Primary Care-Sensitive Condition Hospitalizations (PCSCH), between 2008 and 2023, in the state of São Paulo (Research, Society and Development, 2024)
Primary Care-Sensitive Condition Hospitalizations (PCSCH) have been used as an indirect indicator of the quality of the first level of health care and are part of a strategy to improve the planning and management of health services by authorities. The context of the COVID-19 pandemic led to an unprecedented situation in several municipalities in the state of São Paulo: the reduction of opening hours and the closure of Basic Health Units (UBSs), creating difficulties for the population in accessing Primary Care. Several studies point to several factors that can interfere with PCSC, including opening hours and access barriers, ranging from geographic barriers to the supply of professionals and services. Considering that access to UBSs was impaired during the pandemic, it is possible that there will be an impact on PCSCH occurring in the state. In this sense, the aim is to describe the evolution of PCSCH in the state of São Paulo, between 2008 and 2023. This is an ecological, quantitative and descriptive study, with data of secondary origin, obtained from the SUS Hospital Information System (SIH/SUS), available in the government database DATASUS. The final results demonstrate that there was a decrease in PCSCH over the years, accentuated during the pandemic period, and a subsequent increase in PCSCH in the years 2022 and 2023. With the results, we intend to contribute to the knowledge of the profile of these hospitalizations, which has not yet been studied, and to support the organization of actions in order to minimize them.